2016
DOI: 10.1038/jhh.2016.42
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hypertension, pre-diabetes or both: which is best at predicting cardiovascular events in the long term?

Abstract: The present study aimed to assess the value of pre-diabetes and pre-hypertension in predicting cardiovascular events. A population-based, cross-sectional survey was conducted, representing a large sample of the general Iranian population aged 35 years and older from the Isfahan Province and determined using a random, multistage cluster-sampling 10-year cohort. The five end points considered as study outcome were unstable angina (UA), acute occurrence of myocardial infarction (MI), sudden cardiac death (SCD), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
2
10
0
1
Order By: Relevance
“…Besides that, it is expected the higher proportion of hypertension among diabetic individuals (15.1%) than normotensive groups (2.9%). These results are in agreement with the literature, and the relationship among obesity, hyperlipidemia, diabetes, and high levels of BP has been shown in several studies [5,6,8,9,11,12,17,2123]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Besides that, it is expected the higher proportion of hypertension among diabetic individuals (15.1%) than normotensive groups (2.9%). These results are in agreement with the literature, and the relationship among obesity, hyperlipidemia, diabetes, and high levels of BP has been shown in several studies [5,6,8,9,11,12,17,2123]. …”
Section: Discussionsupporting
confidence: 93%
“…In the last years, epidemiological studies have shown that higher levels of BP are widely associated with increased risk of fatal and nonfatal cardiovascular events [25]. Hypertension is a highly prevalent disease, affects about 1.13 billion adults worldwide [6], and is associated with several cardiometabolic conditions such as hyperlipidemia, atherosclerosis, inflammation, insulin resistance, diabetes mellitus, and obesity [4,5,710]. …”
Section: Introductionmentioning
confidence: 99%
“…The current study confirms previous reports demonstrating that adherence to the DASH diet is not associated with diminished rates of CVD incidence (4) and/or mortality (4,40) . These findings have been primarily confirmed not only in Mediterranean populations but also in Western populations which are not indigenous to the Mediterranean region.…”
Section: Females Malessupporting
confidence: 92%
“…CVD constitute one of the prevailing causes of morbidity and mortality in developed countries (1,2) . Several nonmodifiable and modifiable demographic, lifestyle and clinical factors (including obesity (especially abdominal obesity), dyslipidaemia, the metabolic syndrome and/or type 2 diabetes mellitus) (3,4) alike are implicated in the onset, further progression and, ultimately, attributable mortality of CVD (5) . Although not constituting the initial triggers in all cases, both the aforementioned non-modifiable and modifiable factors are hypothesised to be implicated via a complex interplay in disease onset and propagation through the positive feedback mechanisms of the dysregulated renin-angiotensin-aldosterone system, leading to the activation of an inflammatory cascade and lipid dysregulation (6) .…”
Section: Mediterranean Diet Dietary Approaches To Stop Hypertension Diet Cvdmentioning
confidence: 99%
“…These findings are consistent with those of some of the previous studies. A cohort study from Iran showed that prediabetes status did not predict any CVD events after adjusting for sex and age (17). The Innovation to Reduce Cardiovascular Complications of Diabetes at the Intersection Study (ARTEMIS) showed that among patients with coronary artery disease, prediabetes was not associated with the risk of cardiovascular and all-cause mortality (18).…”
Section: Discussionmentioning
confidence: 99%